XPS Study on Calcining Mixtures of Brucite with Titania - Sánchez Zambrano, Karla Sofía; Hernández Reséndiz, Marina; Gómez Rodríguez, Cristian; García Quiñonez, Linda Viviana; Aguilar Martínez, Josué Amilcar; Rodríguez Castellanos, Edén Amaral; Verdeja, Luis Felipe; Fernández González, Daniel; Castillo Rodríguez, Guadalupe Alan (Molecular Diversity Preservation International, 2022)
In this work, we studied the phases in a Mg-Ti-O system using a 1:1 formulation of MgO:TiO2, mixing synthetic brucite of Mexican origin with TiO2 microparticles of high purity, with a heat treatment at 1100 °C for 1 h. Due to its valence electrons, TiO2 can contribute to the sintering process to improve density in MgO products. The raw materials and formulation by XPS and X-RD techniques were characterized. The results demonstrate the presence of different oxidation states in titania and the formation of different oxides in the Mg-Ti-O system when mixed and calcined at 1100 °C; additionally, we estimated the formation of vacancies in the crystal lattice during the transformation from hexagonal brucite to magnesia with a cubic structure centered on the faces. Its thermal behavior is indicated by the MgO-TiO2 phase diagram.